Analysis of operating modes of single-phase current source rectifier with rectangular-stepped pulse-width modulation - Krasnov, Oleksii; Liubarskyi, Borys; Bozhko, Vladimir; Petrenko, Оleksandr; Dubinina, Oksana; Nuriiev, Ramil (Технологический центр, 2018)
The operating modes of the single-phase active current-source rectifier in the case of rectangular-stepped pulse-width modulation and load in the form of DC traction motor are investigated. The single-phase bridge rectifier circuit with a discharge diode is considered. The mathematical model of the rectifier is developed and the main ratios for pulse-width modulation with rectangular-stepped modulating signal are determined. On the computer model, electromagnetic processes at three modulation frequencies (900, 1,200, 1,800 Hz) are studied. The features of the effect of the modulation depth and frequency on the rectifier power factor and the total harmonic voltage and current distortion in the mains supply are determined. The DC motor for today remains the main type of the traction motor of the 25 kV, 50 Hz AC mainline electric locomotives of alternating current in Ukraine and in some other countries. To power such motors, diode or thyristor rectifiers are used. At the same time, it is known that converters on fully controlled semiconductor devices provide higher power efficiency. The studies allow determining what values of modulation frequency and depth provide a high power factor (more than 0.9) and minimum total harmonic voltage and current distortion distortions in the mains supply. This allows finding rational approaches to the selection of power circuits and control algorithms for active converters in the traction electric drive of electric locomotives. The efficiency of increasing the power factor and reducing the total harmonic voltage and current distortion can be achieved, first of all, by reducing the power consumption for traction of trains. According to the set of selected comparison criteria, the active current-source rectifier with a modulation frequency of 1,200 Hz is the most suitable for implementation in the traction electric drive of the electric locomotive. Provision of high power characteristics in a wide range of traction loads can be achieved in the multi-zone circuit of such a converter.

Дослiджено режими роботи однофазного активного випрямляча струму у випадку широтно-iмпульсної модуляцiї по прямокутно-ступiнчатому закону i навантаження у виглядi тягового двигуна постiйного струму. Розглянуто однофазну мостову схему випрямляча з розрядним дiодом. Розроблено математичну модель випрямляча i визначено основнi розрахунковi спiввiдношення для широтно-iмпульсної модуляцiї при прямокутно-ступiнчатiй формi модуляцiйного сигналу. На комп’ютернiй моделi дослiджено електромагнiтнi процеси при трьох значеннях частоти модуляцiї (900, 1200, 1800 Гц). Встановлено особливостi впливу глибини i частоти модуляцiї на коефiцiєнт потужностi випрямляча i ступiнь спотворення синусоїдальностi форми кривих напруги та струму в мережi живлення. Двигун постiйного струму на сьогоднi залишається основним типом тягового двигуна магiстральних електровозiв змiнного струму напругою 25 кВ, 50 Гц в Українi та в рядi iнших країн. Для живлення таких двигунiв як правило застосовують випрямлячi на дiодах або тиристорах. Разом з тим вiдомо, що перетворювачi на повнiстю керованих напiвпровiдникових приладах забезпечують бiльш високу енергетичну ефективнiсть. Проведенi дослiдження дозволили встановити, при яких значеннях частоти i глибини модуляцiї забезпечується високий коефiцiєнт потужностi (бiльше 0,9) i мiнiмальнi спотворення синусоїдальностi форми напруги i струму в мережi живлення. Це дозволяє визначити рацiональнi пiдходи до вибору силових схем i алгоритмiв управлiння активними перетворювачами в тяговому електроприводi електровозiв. Ефективнiсть пiдвищення коефiцiєнта потужностi i зменшення несинусоїдальностi напруги та струму полягає, насамперед, в зниженнi витрат електроенергiї на тягу поїздiв. За сукупнiстю обраних критерiїв порiвняння найбiльш прийнятним для реалiзацiї в тяговому електроприводi електровоза є активний випрямляч струму з частотою модуляцiї 1200 Гц. Забезпечення високих енергетичних характеристик в широкому дiапазонi тягових навантажень може бути досягнуто в багатозоннiй схемi такого перетворювача.
Аналіз режимів роботи однофазного активного випрямляча струму з широтно-імпульсною модуляцією по прямокутно-ступінчатому закону
Keywords: active current-source rectifier; power factor; pulse-width modulation; mathematical model; активний випрямляч струму; коефiцiєнт потужностi; широтно-iмпульсна модуляцiя; математична модель